Staphylococcus aureus Endocarditis with Multivalvular Involvement Secondary to an Atrial Septal Defect - Vistasp Jimmy Daruwalla; Jahnavi Sagi; Hassan Tahir; Srikanth Penumetsa (Case Reports in Cardiology)
Infective endocarditis is usually diagnosed using modified Duke’s criteria. Our patient had a subacute presentation and a low suspicion for endocarditis during admission, unfortunately leading to her death. Despite advances in diagnostic and therapeutic measures including antibiotic therapy and surgical techniques, morbidity and mortality with staphylococcal infective endocarditis remain high. Hence, we stress the significance of having a low threshold for TEE in patients with multisystem involvement due to Staphylococcus aureus that have evidence of persistent infection despite antibiotic treatment, even if the suspicion for endocarditis is low based on Duke’s criteria. TEE substantially improves the sensitivity of diagnosis but may not be readily available in many medical centers. Presence of an ASD has been noted to have increased the risk of left sided endocarditis even with conditions that predispose to right sided endocarditis, particularly in patients with hemodialysis and diabetes as morbid risk factors.